2011
DOI: 10.1089/ars.2010.3772
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Biology of B-Cell Leukemia/Lymphoma 2/Adenovirus E1B Interacting Protein 3 and Nip-Like Protein X

Abstract: B-cell leukemia/lymphoma 2 (BCL-2)/adenovirus E1B interacting protein 3 (BNIP3) and Nip-like protein X (NIX) are atypical BCL-2 homology domain 3-only proteins involved in cell death, autophagy, and programmed mitochondrial clearance. BNIP3 and NIX cause cell death by targeting mitochondria, directly through BCL-2-associated X protein-or BCL-2-antagonist/killer-dependent mechanisms, or indirectly through an effect on calcium stores in the endoplasmic reticulum. BNIP3 and NIX also induce autophagy through an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 109 publications
(159 reference statements)
3
28
0
Order By: Relevance
“…Previous studies have reported on the role of BNIP3, a BH3-only protein, as regulators of both autophagy and apoptosis in response to hypoxic signaling in cardiac disorders and in cancer. 47,48 However, our findings suggest that the oxidative stress-altered BOK-MCL1 rheostat is the key inducer of autophagy in PE as we were unable to detect altered levels of BNIP3 in PE placentas (data not shown), suggesting that this BH3-only protein may have distinct tissue-specific functions.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have reported on the role of BNIP3, a BH3-only protein, as regulators of both autophagy and apoptosis in response to hypoxic signaling in cardiac disorders and in cancer. 47,48 However, our findings suggest that the oxidative stress-altered BOK-MCL1 rheostat is the key inducer of autophagy in PE as we were unable to detect altered levels of BNIP3 in PE placentas (data not shown), suggesting that this BH3-only protein may have distinct tissue-specific functions.…”
Section: Discussionmentioning
confidence: 63%
“…BNIP3 and the closely related protein NIX (approximately 50% identical amino acids) are single-pass, transmembrane proteins, located in the OMM (reviewed in [72]) (Fig. 2).…”
Section: Bnip3 and Nix: Multifunctional Outer Mitochondrial Membrane mentioning
confidence: 99%
“…One of the critical points in mitophagy is how the autophagy machinery targets to mitochondria to specifically sequester the energy-converting organelles. Recent studies reveal key proteins that localize to the mitochondrial surface and establish the selectivity of mitochondrial degradation in yeast and mammals (5)(6)(7). In principle, it has so far been hypothesized that those key molecules directly or indirectly participate in recruiting core Atg proteins required for generation of isolation membranes and subsequent formation of autophagosomes.…”
mentioning
confidence: 99%